Complications Are Infrequent After Humeral Shaft Fractures Due to Low-Energy Gunshot Injuries. Issue 3 (March 2023) - Cho, Elizabeth; Taylor, Aaron; Olson, Jeffrey J.; Entezari, Vahid; Vallier, Heather A.
Abstract : Objective: To describe humerus shaft fractures after low-energy gunshot wound (GSW) and compare with blunt injuries. We hypothesized that nerve injury, infection, and fracture union would be similar. Design: Retrospective. Setting: Urban Level 1 trauma center. Patients/Participants: Four hundred three patients were treated for a humeral shaft fracture over 18 years. Sixty-two patients sustained injury due to GSW. Intervention: Primary open reduction and internal fixation was pursued in 59%, including 32% after GSW. Main Outcome Measurements: Rates of nerve injury, infection, and fracture union. Results: Patients with GSW were younger with a mean age of 30 years, more likely male (90%), with isolated injuries (84%), and less likely to have simple fractures (84%). Both groups experienced high rates of union (98% of GSW fractures vs. 99% of closed high-energy fractures). Deep infection occurred in 1 patient (1.6%) after GSW. Rates of deep infection in the closed and open blunt trauma fracture groups were similarly low at 1% and 4.5%, respectively. Nerve injury on presentation after GSW was more common than after low-energy and high-energy closed fractures (47% vs. 13% and 27%), but similar to blunt open fracture (52%). Despite higher rates of nerve injury, nerve recovery occurred at similarly high rates after both GSW and blunt injuries (78% vs. 86%). Conclusions: Nerve injuries are more common after GSW, but most recover without intervention. Infection is uncommon after GSW, and secondary unplanned operations are rare. Initial nonoperative care of most GSW humerus fractures, even with radial nerve injury at the time of presentation, seems appropriate. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.